1997
DOI: 10.1046/j.1365-2958.1997.2981663.x
|View full text |Cite
|
Sign up to set email alerts
|

Replication of minichromosomes in a host in which chromosome replication is random

Abstract: SummaryMinichromosomes are plasmids with the origin of chromosome replication, oriC, as their only origin of replication. In Escherichia coli, minichromosomes are compatible with the chromosome and replicate in a cell-cycle-specific manner at the same time as oriC located on the chromosome initiates replication. In int strains, oriC has been inactivated and replaced by a plasmid origin. Because plasmids control their own replication, chromosome replication is uncoupled from the normal cell-cycle control and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…It should also be mentioned that oriC minichromosomes retain a cell cycle‐specific replication pattern in a host in which chromosome replication is random in time, as shown by Eliasson et al. (1997) with a so‐called intP1 strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be mentioned that oriC minichromosomes retain a cell cycle‐specific replication pattern in a host in which chromosome replication is random in time, as shown by Eliasson et al. (1997) with a so‐called intP1 strain.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be mentioned that oriC minichromosomes retain a cell cycle-specific replication pattern in a host in which chromosome replication is random in time, as shown by Eliasson et al (1997) with a so-called intP1 strain. This raises critical questions about the ability of the initiator titration model to explain the control of chromosome replication fully.…”
Section: Synchrony Sequestration and Eclipsementioning
confidence: 99%
“…Consistent with this, major effects of transertion on the microviscosity of the membrane have been shown via inhibition of transcription and translation (Binenbaum et al, 1999). The second problem, the nature of the mechanism that initiates chromosome replication, is another long-standing mystery (Eliasson and Nordström, 1997; Wang et al, 2011). This mechanism in E. coli is generally attributed to the relative proportions of the DnaA ‘initiator’ protein in the ATP-DnaA form, which is active in initiation, and the ADP-DnaA, which is inactive (Castuma et al, 1993).…”
Section: Hyperstructuresmentioning
confidence: 99%
“…Synchronous cell-cycle replication of up to 30 additional oriC copies is permitted, demonstrating that the levels of diffusible factors are not generally limiting (151). Cell cycle-specific minichromosome replication is not dependent on chromosomal oriC function, and minichromosomes are retained in cells with randomly replicating chromosomes, in which chromosomal oriC is replaced by a plasmid replication origin (62). Combined, these studies demonstrated that the wt oriC sequence contains all of the information needed to direct cell cycle-specific timing of initiation.…”
Section: Factors Involved In Initiation Of Chromosome Replicationmentioning
confidence: 99%